Myśli Jana Jakuba Rousseau o wychowaniu i muzyce – ich reminiscencje w rytmice Emila Jaques-Dalcroze’a - Ewa Szatan (Problemy Wczesnej Edukacji)
The text is an attempt to analyze and interpret a selection of Jean-Jacques Rousseau’s thoughts about education relating to music education, the thoughts that I find as reminiscences of assumptions and methods of Emil Jaques-Dalcroze. He focuses his discourse on the issues related to the moment when the musical education of the child takes form and also on the quality of the child’s first contacts with music, and the role of parent and teacher in the child’s appreciation of music. A comparison of the assumptions regarding musical education of Rousseau and Jaques-Dalcroze may seem interesting, because, despite the passage of successive decades, they seem to be still valid, as, for example, the one that speaks of the joy of discovery that should accompany the child in the learning process.